Strategi dan Inovasi Peningkatan Pendapatan Asli Daerah dari Sektor Pajak Daerah Melalui E-Regional Income (Kajian di Pemerintah Kota Pekalongan) - Septiadi, Andi (Jurnal Ekonomi dan Bisnis, 2024)
Regional Own Revenue (PAD) makes an important contribution to the Regional Revenue and Expenditure Budget (APBD) to finance the implementation of administrative processes, government services, and regional development. Therefore it takes creation, strategy, and innovation in its management. This writing aims to discover how the Pekalongan City Government's creations and innovations increase PAD. This study uses a qualitative descriptive method. The data collection techniques used included observation, interviews with Regional Apparatus Organizations (OPD) as PAD managers, and documentation in the form of secondary data, including APBD, PAD, and other relevant data. The results of the study show that the creations, strategies, and innovations carried out include implementing QRIS in paying taxes, digitizing tax services, and installing tapping boxes in restaurants which can increase PAD, however, the contribution of PAD to regional income during the 2018-2023 period is still relatively small, namely an average of 22.68%.